Islamic Education in Thailand Pattani Muslim Minority: What are the Institutional Continuity and Change? - Wekke, Ismail Suardi; Siddin, Siddin; Langputeh, Sukree (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2019)
National aspiration in different ways effects to the community response through their condition. This situation reflects the dynamics of interest in diverse direction. Therefore, this article will identify the development of Muslim minority in Pattani, Thailand. A qualitative approach was applied to conducting research. In-depth interview and non-participant observation was an instrument to collect data. Data triangulation was conducted through twice focus group discussions in a different university. This article discusses the portrait of Islamic education in Pattani of Thailand. They face dynamic and struggle to maintain a combination of national interest and local need. National aspiration is the main source to formulate the institutional design. On the other hand, they embedded local aspiration through ethnic and religious values to combine in national education. In keeping with the identities and personal communication, they tried to root the religious value and belief to educational form. Finally, this article amplifies the local condition in Pattani Muslim society. The development of Islamic education runs to the situation in extending ethnic, religious expression, and politic.